DETERMINANTS OF SYNOVIAL FLUID LOSS AND ALTERATION IN THE TEMPOROMANDIBULAR JOINT: A SYSTEMATIC REVIEW OF MOLECULAR BIOMARKERS (REMUNOM, 2026)
This systematic review comprehensively identifies and critically analyzes the determinant factors associated with the loss, alteration, or dysregulation of synovial fluid (SF) homeostasis within the temporomandibular joint (TMJ). A rigorous systematic review was conducted in accordance with PRISMA guidelines, searching PubMed/MEDLINE, Europe PMC, LILACS, and SciELO up to January 11, 2026. From 5,361 initial records, 32 studies were included for qualitative synthesis. The collective evidence consistently highlighted the pivotal role of inflammatory mediators in driving SF alterations. Elevated levels of proinflammatory cytokines (IL-6, IL-8, TNF-α) were frequently reported in patients with internal derangement and osteoarthritis. Vascular Endothelial Growth Factor (VEGF) demonstrated a significant correlation with articular degeneration, and MRI-detected joint effusion was strongly associated with increased concentrations of inflammatory biomarkers. The Dickkopf-related protein 1 (DKK1) emerged as a critical modulator in TMJ OA pathogenesis, with its levels significantly decreasing following therapeutic interventions with hyaluronic acid. The pathogenesis of SF loss and alteration in the TMJ is complex and multifactorial, primarily driven by a cascade of inflammatory mediators, enzymatic degradation, and mechanical stress. Therapeutic strategies aimed at modulating these inflammatory pathways and restoring SF composition, such as arthrocentesis and hyaluronic acid supplementation, demonstrate promising clinical benefits.